Physical activity and nutrition education at the school environment aimed at preventing childhood obesity: evidence from systematic reviews - Paulo Henrique Guerra; Jonas Augusto Cardoso da Silveira; Emanuel Péricles Salvador (Jornal de Pediatria, 2016)
Objective: To organize the main findings and list the most frequent recommendations from systematic reviews of interventions developed at the school environment aimed at reducing overweight in children and adolescents. Data source: Searches for systematic reviews available until December 31, 2014 were conducted in five electronic databases: Cochrane, PubMed, SciELO, SPORTDiscus, and Web of Science. Manual search for cross-references were also performed. Summary of the findings: Of the initial 2139 references, 33 systematic reviews adequately met the inclusion criteria and were included in the descriptive summary. In this set, interventions with periods of time greater than six months in duration (nine reviews), and parental involvement in the content and/or planned actions (six reviews) were identified as the most frequent and effective recommendations. Additionally, it was observed that boys respond more effectively to structural interventions, whereas girls respond to behavioral interventions. None of the included reviews was able to make inferences about the theoretical basis used in interventions as, apparently, those in charge of the interventions disregarded this component in their preparation. Conclusions: Although the summary identified evidence with important applications in terms of public health, there are still gaps to be filled in this field of knowledge, such as the effectiveness of different theoretical models, the identification of the best strategies in relation to gender and age of participants and, finally, the identification of moderating variables to maximize the benefits provided by the interventions. Resumo: Objetivo: Organizar os principais achados e elencar as recomendações mais frequentes das revisões sistemáticas de intervenções desenvolvidas no ambiente escolar com fins na redução do excesso de peso em crianças e adolescentes. Fonte dos dados: Buscas por revisões sistemáticas disponíveis até 31 de Dezembro de 2014 foram realizadas em cinco bases de dados eletrônicas: Cochrane, PubMed, SciELO, SPORTDiscus, e Web of Science. Buscas manuais por referências cruzadas também foram desenvolvidas. Síntese dos dados: Das 2.139 referências iniciais, 33 revisões sistemáticas responderam adequadamente aos critérios de inclusão e compuseram a síntese descritiva. Neste conjunto, identificou-se como recomendações mais frequentes e efetivas intervenções que possuem períodos de tempo superior a seis meses de duração (9 revisões), e o envolvimento dos pais nos conteúdos e/ou ações previstas (6 revisões). Além disso, observou-se que meninos respondem de forma mais efetivas as intervenções estruturais enquanto as meninas às intervenções comportamentais. De modo consistente entre as revisões incluídas, nenhuma delas conseguiu realizar inferências sobre a base teórica utilizada nas intervenções, uma vez que, aparentemente, os responsáveis pelas intervenções desconsideraram esse componente em sua elaboração. Conclusões: Embora a síntese tenha identificado evidências com aplicações importantes em termos de saúde coletiva, ainda existem lacunas a serem preenchidas nesse campo do conhecimento, tais como a efetividade de diferentes modelos teóricos, o reconhecimento das melhores estratégias em relação ao sexo e a idade dos participantes e, por fim, a identificação de variáveis moderadoras para potencializar os benefícios proporcionado pelas intervenções. Keywords: Review, Children, Physical activity, Nutrition education, Overweight, School, Palavras-chave: Revisão, Crianças, Atividade física, Educação nutricional, Sobrepeso, Escola